FEASIBILITY OF SOYBEAN FARMING IN INDONESIA: A SYSTEMATIC LITERATURE REVIEW - Prihtanti, Tinjung Mary (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2023)
Soybeans are an essential commodity in the Indonesian economy; therefore, the government encourages soybean cultivation at the farmer level. This article aims to analyze variations in the feasibility level of soybean farming in Indonesia, the distribution of R/C values, and its forming parameters based on the results of a research literature review. This paper also attempts to look at the factors that influence R/C achievement and provide input for similar studies in the future. Literature was taken from the Google Scholar database, which published research on the feasibility of soybean farming in Indonesia, published in journals or proceedings, both in Indonesian and English, and published in 2013-2023. A total of 122 articles were screened, around 51 (113 case studies) for further explanation, consisting of 39 journal articles and 12 proceedings articles. The analysis technique uses CV (coefficient of variation) and simple tabulation. All articles concluded that soybean farming was worth cultivating (R/C > 1), but three articles received an R/C value < 1, or soybean farming was not worth cultivating. The highest R/C value is 3.96, and the lowest is 0.50. In contrast, the CV value of R/C shows the lowest value (of 0.33) compared to the CV values of TR, TC, productivity, and selling price of harvest, meaning the distribution The R/C value of soybean farming over the last ten years tends to be homogeneous (does not vary). High productivity does not indicate high R/C achievement, nor do certain superior varieties always show high R/C. Farming feasibility research needs to explain more fully the parameters that form R/C values, use standard writing standards in writing the units for each parameter, and explain varieties, cultivation techniques, and the conditions of farmers in soybean farming.